[Fidel V. Ramos ; Miriam Defensor Santiago ; Willie Nepomuceno [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Leading Presidential Candidate Fidel Ramos is put on the defense with charge about his involvement in the Martial Law regime. Rumors about Miriam Santiago's insanity are widespread. Willie Nepomuceno mimicking political figures.